Urolithiasis Frequency and Risk Factors in Home Ventilated Patients with Tracheostomy - İlknur Tolunay; R. Dinçer Yıldızdaş; Özden Özgür Horoz; Engin Melek; Bahriye Atmış; Bilgin Yüksel; İhsan Turan (Galenos Yayinevi, 2017)
Introduction: The aim of this study was to assess the frequency of urolithiasis and risk factors for urolithiasis in home ventilated patients with tracheostomy. Methods: We retrospectively analyzed 30 home-ventilated patients with tracheostomy who were followed up at our pediatric intensive care unit from January 2014 to December 2015. Data analyzed included age, gender, underlying disease for hospitalization, drugs, nutrition method, nutrition solution, biochemical parameters, 25(OH) vitamin D and paratyroid hormone levels, urinary calcium/creatinine ratio, and urinary ultrasonography results. Results: A total of 30 patients [9 female (30%), 21 male (70%)] with a median age of 90.06 months (15-197) were evaluated in this study. According to the motor function classification system, 33.3% (10/30) of patients were class 4 and 66.7% (20/30) were class 5 and all patients were immobile. Upper urinary stone was detected with urinary ultrasonography in 30% (9/30) of patients. Urinary calcium/creatinine ratio was >0.21 in 56.7% (17/30) of patients. Age-related urinary calcium/creatinine ratio was above the normal limits in 66.6% (20/30) of patients. The mean daily calcium intake was 54±82 (336-1200) mg/day and vitamin D intake was 25.9±10.6 (7.8-51.4) μg/day. Blood calcium was normal (8.5-10.5 mg/dL) in all patients. Blood 25(OH) vitamin D level was >30 ng/mL in 8 patients, 20-30 ng/mL in 13 patients and <20 ng/mL in 9 patients. Conclusion: In our study, immobilization was the most important factor for urolithiasis in home ventilated patients with tracheostomy and these patients need to be followed closely in terms of accompanying metabolic disorders.